Does laryngopharyngeal reflux affect voice quality? a cross-sectional study - Vakil, Almas J.; Vyas, Pratibha; Prasad, Shreya; Singh, Praveen (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Laryngopharyngeal reﬂux (LPR) is a rising disease that leads to voice changes. This study aimed to assess the potential association between the symptoms of laryngopharyngeal reflux (LPR) and voice disorders using the Reflux symptom index (RSI) and the Voice handicap index (VHI-10) scales, respectively. Methods: This cross-sectional study was conducted in the Department of Otorhinolaryngology at Mahatma Gandhi Medical College and Hospital, Jaipur, India, from June 2019 to November 2019, on a sample size of 144 patients having complaints related to voice change and laryngopharyngeal reflux. The participants filled the RSI and the VHI-10 questionnaires. RSI scores of >13 and VHI-10 scores of >11 indicated LPR-related symptoms and voice disorders, respectively. Results: The study included 70 (48.61%) patients who were males and 74 (51.38%) patients who were females. The mean age was 33.5 years. Overall, 89(61.80%) patients had RSI scores of >13 while 102 (70.83%) patients had VHI-10 scores of >11. A significant association was found between positive RSI and VHI-10 scores (p<0.001). Conclusions: A significant association between RSI and VHI-10 scores reflects an association of laryngopharyngeal reflux with long-standing voice change. RSI and VHI-10 may constitute valuable tools in diagnosing suspected patients with voice change and direct early start of empirical therapy with PPI.